Microstructure development during thermomechanical treatment of Al-Mg-Si alloy - Martinova Z.; Zlateva G. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The effect of natural aging and 95% cold deformation on the microstructure evolution and aging characteristics in commercial Al - 1 mass % Mg2Si alloy subjected to thermomechanical treatment (TMT) was examined. Transmission electron microscopy observations, tensile tests and electrical conductivity measurements were carried out in order to correlate microstructural features to properties on each TMT step. It was established that pre-aging at room temperature affected the morphology of dislocation structure induced by next cold deformation. The observed transition from cellular to homogenous dislocation distribution was explained by the different stability of zones produced by pre-aging of different duration. Natural aging suppressed recovery processes during post-deformation artificial aging, especially after prolonged storage after quenching and at lower aging temperature. It influenced the morphology of precipitates produced by post deformation artificial aging also. The overall effect of TMT involving prior-deformation natural aging in the scheme, on hardness, tensile properties and electrical conductivity is discussed based on experimental microstruture observations.